2022
DOI: 10.3389/fphys.2022.847267
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Supervised Deep Learning for Tooth-Marked Tongue Recognition

Abstract: The recognition of tooth-marked tongues has important value for clinical diagnosis of traditional Chinese medicine. Tooth-marked tongue is often related to spleen deficiency, cold dampness, sputum, effusion, and blood stasis. The clinical manifestations of patients with tooth-marked tongue include loss of appetite, borborygmus, gastric distention, and loose stool. Traditional clinical tooth-marked tongue recognition is conducted subjectively based on the doctor’s visual observation, and its performance is affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The theory of TCM suggests that changes detected using tongue images (the colour, size and shape of the tongue and the colour, thickness and moisture content of the tongue coating) can reflect the health state of the human body, which is especially closely related to gastric diseases. 4 , 5 , 6 Recent studies have shown that changes in tongue images and tongue coatings are closely related to the oral/tongue coating microbiome. 7 Additionally, many studies have confirmed that the oral/tongue coating microbial group has good diagnostic value for pancreatic cancer, 8 liver carcinoma, 9 colorectal cancer 10 and other tumours, as well as gastritis, 11 rheumatoid arthritis, 12 chronic hepatitis B 13 and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of TCM suggests that changes detected using tongue images (the colour, size and shape of the tongue and the colour, thickness and moisture content of the tongue coating) can reflect the health state of the human body, which is especially closely related to gastric diseases. 4 , 5 , 6 Recent studies have shown that changes in tongue images and tongue coatings are closely related to the oral/tongue coating microbiome. 7 Additionally, many studies have confirmed that the oral/tongue coating microbial group has good diagnostic value for pancreatic cancer, 8 liver carcinoma, 9 colorectal cancer 10 and other tumours, as well as gastritis, 11 rheumatoid arthritis, 12 chronic hepatitis B 13 and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the symptoms on the tongue are very difficult to automatically identify or quantify, which has become a core challenge in SD. In recent years, many studies in this area have paid much attention to using deep learning methods to automatically classify or identify tongue symptoms, like tooth-marked tongue, 11 , 15 , 103 105 , 110 , 111 tongue coating, 10 , 16 , 31 , 42 , 112 , 113 coating color, 66 , 113 , 114 tongue color, 22 , 113 , 115 cracked tongue, 9 , 110 , 111 , 116 , 117 sublingual vein, 10 and fungiform papillae on tongue. 118 …”
Section: Tongue Image For the Symptom (Sign) Differentiationmentioning
confidence: 99%
“…Similarly, they utilized this method to classify rotten greasy coating of the tongue 16 and cracked tongue 116 based on the deep features, which outperforms other state-of-the-art methods. Another tooth-marked classification model based on image-level annotation was proposed by Zhou et al, 105 and it could also locate the tooth-marked area with the weakly supervised method. When classifying coating features, Wang et al 31 proposed a GreasyCoatNet framework that could classify three-level greasy coating robustly, indicating the potential ability to quantify tongue greasy coating.…”
Section: Tongue Image For the Symptom (Sign) Differentiationmentioning
confidence: 99%
“…Hou et al conducted research on the classification of tongue color based on CNN with a data set of 1500 tongue images, and the accuracy rate was 89% [20]. In addition, some scholars have conducted methodological studies for different subtasks of tongue diagnosis, such as tongue color, fissure, tongue shape, and tongue coating [21][22][23][24][25][26][27]. The above study achieved high accuracy of tongue diagnosis based on TIAI.…”
Section: Introductionmentioning
confidence: 97%